Towards a low-carbon society: A review of lithium resource availability, challenges and innovations in mining, extraction and recycling, and future perspectives - Tabelin, Carlito Baltazar; Dallas, Jessica; Casanova, Sophia; Pelech, Timothy; Bournival, Ghislain; Saydam, Serkan; Canbulat, Ismet (Minerals engineering, 2021)
•The LIBs market is forecasted to reach at least US$221 B by 2024 using 20–25% CAGR.•Li production growth within the next five years will lag that of demand.•Major Li resources are found in Argentina, Australia, USA, Chile, Bolivia & China.•Current technologies for end-of-life LIBs recycling remain inefficient.•Waste streams, clays and geothermal brines are promising future Li resources. The demand for lithium has skyrocketed in recent years primarily due to three international treaties—Kyoto Protocol, Paris Agreement and UN Sustainable Development Goals—all of which are pushing for the integration of more renewable energy and clean storage technologies in the transportation and electric power sectors to curb CO2 emissions and limit the adverse effects of CO2-promoted climate change. Over 60% of lithium produced in 2019 were utilised for the manufacture of lithium-ion batteries (LIBs), the compact and high-density energy storage devices crucial for low-carbon emission electric-based vehicles (EVs) and secondary storage media for renewable energy sources like solar and wind. In 2019, the global market value of lithium reached around US$213 B and is forecasted to grow by around 20–25% until 2025. In this review, the current state of global lithium resources, global lithium material flow, and forecasts of future lithium supply–demand dynamics are discussed. Persistent challenges in mining, processing and industrial-scale recycling operations are also examined and recent innovations to address these issues are introduced. Finally, unconventional lithium sources like submarine/deep-sea ferromanganese (Fe-Mn) nodules and crusts, industrial wastes (e.g., desalination brines, geothermal brines and coal fly ashes), mining wastes and effluents, and extra-terrestrial materials are explored.